4th EuroITV 2013 workshop on Interactive Digital TV in emergent economies - Thinking outside the TV box - De Lucena Jr, V.; Lugmayr, Artur; Yu, Z.; Pal, A. (2013)
The popularity of TV worldwide and particularly in emergent markets opened a window of opportunities for many people working with Interactive Digital TV and related topics. New solutions and new business approaches are supposed to rise from this scenario, creating many new job opportunities. The main goal of this workshop is to bring together researchers, educators, and industry related people working in the deployment of solutions for DTV Systems and associated Applications in emergent countries. Along this workshop, discussion about the adopted policies, technologies, state-of-the-art, middleware solutions, content models, interactivity systems, and future applications in the researchers' countries are going to be the main action. Indeed, it is going to be a global forum where the participants will be able to identify common issues and exchange experiences, sharing the adopted solutions for common known problems. The organizers hope to keep building and maintaining a research network that will help people working in developing countries to increase their technical contributions in Interactive Digital TV related issues.